Answer:
x can be any real number.
Step-by-step explanation:
- 4 (x - 1) = - 3x + 13 - 9 - x
The easiest approach to solving this problem is to simplify each side. Start by focusing on the left side, distribute the term outside of the parenthesis, multiply every term inside the parenthsis by the term outside of it,
- 4 ( x - 1 ) = - 3x + 13 - 9 - x
Distribute,
(-4)(x) + (-4)(-1) = - 3x + 13 - 9 - x
Simplify,
-4x + 4 = - 3x + 13 - 9 - x
Simplify the right side of the equation, combine like terms,
-4x + 4 = - 3x + 13 - 9 - x
Rearrage,
-4x + 4 = -3x - x + 13 - 9
Simplify,
-4x + 4 = -4x + 4
At this point, one should use inverse operations to solve the problem, but the given equation is an identity, meaning that any real value can be substituted into the parameter (x), and the equation will yield a true result. Thus, (x) equals all real numbers.